Penyuluhan penggunaan pakan berwawasan lingkungan kepada pembudidaya keramba jaring apung di Danau Laut Tawar Aceh Tengah (Counseling on the use of environmentally conscious feeding to floating net cage farmers in the Lake Laut Tawar Aceh Tengah) - Adhar, Saiful; Khalil, Munawwar; Muliani, M (Buletin Pengabdian, 2023)
Cultivating Floating Net Cages on Lake Laut Tawar has become an activity supporting the people's economy. The profits obtained by cultivators range from IDR 2.5 7 million per maintenance period. However, on the other hand, this activity can reduce the carrying capacity of the waters of Lake Laut Tawar due to waste pollution originating from leftover feed. One of the impacts is the mass death of fish in the floating net cages. The core problem of this problem is the lack of knowledge of Floating net cage cultivators and workers regarding feed management and water pollution. This problem can be solved by increasing the knowledge of Floating net cage farmers and workers in Lake Laut Tawar. The method used in this activity was counseling on using environmentally friendly feed in the Floating Net Cage system for fish farming in Lake Laut Tawar, Central Aceh. The aim and output targetted of this community service activity were to increase the application of science and technology in the community, in the form of improving the management of the use of fish feed d in floating net cages system. Evaluation of the level of success and satisfaction of participants was carried out using a questionnaire. Based on an analysis of the level of satisfaction and success, 80-90% of farmers are very satisfied with this community service activity. The benefits of this activity provide knowledge and positive motivation for partners in tilapia culture in floating net cages by increasing production as well as protecting the environment from pollution.